Powdery mildew resistance in Kentucky bluegrass ecotypes from Poland. - Czembor, Elżbieta; Feuerstein, Ulf; Żurek, Grzegorz (Plant Breeding and Seed Science, 2001)
A total of 444 ecotypes Kentucky bluegrass (Poa pratensis L.) collected in Poland were screened for resistance to powdery mildew. A field experiment was established at Hof Steimke, DSV (Deutschen Saatveredelung), Germany. The ecotypes originated from Polish Gene Bank, IHAR – Botanical Garden, Bydgoszcz. The average powdery mildew resistance score for tested ecotypes was 4.3, and the same score for eight varieties used as a control was 4.8. From the control varieties (Limousine, Alicja, Julia, Berbie, Ottos, Jori, Eska and Oxford) the most resistant to infection was Limousine. Plants showed resistance scores 5 or 7, on average 6.17. Sixty-two ecotypes (14.0%) which were scored on average more than 6 were included in two groups: with high resistance (15 ecotypes) and with moderate resistance (47 ecotypes). Ecotypes which plants were scored on average less than 6 were included in a susceptible group (scores on average 4.0 – 5.9), and a very susceptible group (scores on average 2.0 – 3.9). There were 226 ecotypes in the susceptible group (50.9%) and 156 (35.1%) in the very susceptible group.High resistance to powdery mildew showed ecotypes collected from nine habitats: meadow, wet meadow, peat meadow, pasture, field, forest, waterside, ditch and roadside. The highest percentage of ecotypes with high resistance was collected from wet meadows. The value of these newly identified highly resistant ecotypes for control of powdery mildew on Kentucky bluegrass is discussed.